Measurement of the top quark mass in the t(t)over-bar -> dilepton channel from root s=8TeVATLAS data - Çetin, Serkant Ali (Elsevier, 2016)
The top quark mass is measured in the t (t) over bar -> dilepton channel (lepton= e, mu) using ATLAS data recorded in the year 2012 at the LHC. The data were taken at a proton-proton centre-of-mass energy of root s = 8 TeV and correspond to an integrated luminosity of about 20.2 fb(-1). Exploiting the template method, and using the distribution of invariant masses of lepton-b-jetpairs, the top quark mass is measured to be m(top) = 172.99 +/- 0.41(stat)+/- 0.74(syst) GeV, with a total uncertainty of 0.84 GeV. Finally, acombination with previous ATLAS m(top) measurements from root s = 7 TeV data in the t (t) over bar -> dilepton and t (t) over bar -> lepton + jets channels results in m(top) = 172.84 +/- 0.34(stat)+/- 0.61(syst) GeV, with a total uncertainty of 0.70 GeV. (C) 2016 The Author. Published by Elsevier B.V.
Keywords: PARTON DISTRIBUTIONS; PAIR PRODUCTION; CROSS-SECTION; PLUS PLUS; FRAGMENTATION; PHYSICS; MODEL; LHC